2005
DOI: 10.1016/j.stam.2004.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Studies on visual sensor from self-assembled polypeptides

Abstract: A silane terminated poly (3-benzyloxycarbonyl-L-lysine) was synthesized and deposited as a self-assembled monolayer on the pre-colored silica substrate which was fabricated by Langmuir-Blodgett (LB) method. The monolayer was covalently attached to silica surface through terminal silane groups. The secondary structure of polymer, a-helix, was confirmed by circular dichroism spectroscopy. Furthermore, the conversion of the monolayer surface from non-ionic to cationic was accomplished by removal of 3-benzyloxycar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…In the presence of the bacteria (1 × 10 5 cfu/mL), the film turned orange due to changes in the thickness of the film. 470…”
Section: Detection Based On Structural Color Changementioning
confidence: 99%
“…In the presence of the bacteria (1 × 10 5 cfu/mL), the film turned orange due to changes in the thickness of the film. 470…”
Section: Detection Based On Structural Color Changementioning
confidence: 99%
“…Previously, we have demonstrated that a silica thin-film constructed on a silicon substrate showed interference color change when bacteria and protein adsorbed on it. [13][14][15][16] Adsorption of bacteria of a sub-micron scale gave a visible color change, which was not only observed by spectrum measurement, but was also seen by the naked eye. On the other hand, adsorption of small molecules on the nanometre scale, such as antigens and peptides, gave little color change, which was only observed by spectrum measurement.…”
mentioning
confidence: 99%
“…Another polymer-based approach uses artificial polypeptides as a color reporting group [167,168]. Peptides with modified groups (e.g.…”
Section: Organic Polymersmentioning
confidence: 99%
“…This is known as structural color because light is reflected based on nanostructures and does not require color pigments. In a sensor reported by Yokogawa and co-workers, lysine-based polymers made from E-benzyloxycarbonyl-L-lysine are immobilized on a silica substrate [167,168]. To modulate the polymer structure, an RNA aptamer for Sphingobium bacteria is absorbed on the cationic polypeptide surface.…”
Section: Assays By Artificial Polypeptidesmentioning
confidence: 99%